The Governance of Downstream Oil Palm Development in the Technopolitan Area of Pelalawan Regency - Rusli, Zaili; Mashur, Dadang; Yozani, Ringgo Eldapi; Habibie, Dedi Kusuma; Simanjuntak, Harapan Tua Ricky Freddy; Saputra, Trio (International Journal of Energy Economics and Policy, 2022)
This study aims to determine the governance of oil palm downstream development in technopolitan areas of Pelalawan Regency. This research method was carried out qualitatively by analyzing the object of study. First, the development of oil palm down streaming in technopolitan areas, second, the potential for oil palm down streaming in technopolitan areas and third, governance of oil palm downstream development in technopolitan areas. The development of downstream oil palm in technopolitan areas facilitates the development of ideas, innovations, and know-how from the utilization of oil palm derivative products that have a high selling value and downstream oil palm becomes a support for government, academia, business and the community in implementing Good Agricultural Practice (GAP). The development of governance oil palm downstream in Pelalawan Regency is implemented in an integrated, competitive and sustainable approach. The development with such governance makes it possible for every stakeholders and the community (independent farmers) to receive economic, social, and environmental benefits from the development of technopolitan areas in Pelalawan Regency.